Inisiatif Hijau Kabupaten Tuban: Implementasi Kebijakan Pelestarian Mata Air dan Hutan Lindung Berbasis Kolaborasi dan Kearifan Lokal - Agus Rianto; Ulul Albab; Sri Kamariyah; Ika Devy Pramudiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study evaluates the implementation of water source conservation and conservation forest policies in Tuban Regency that integrate collaborative methods between various parties and local wisdom. Using a descriptive qualitative approach, data collection was conducted through in-depth interviews with staff from the Environmental Service, representatives of environmental NGOs, traditional leaders, and local communities, coupled with field observations related to the “Adopt a Spring” and “Forest School” programs. The results of the study indicate that the success of the policy is not only supported by local regulations, but also by collaboration involving the government, local communities, the private sector, and educational institutions. Local wisdom, such as the “nyadran sumber” ceremony and traditional protected forest methods, increase the legitimacy and effectiveness of environmental protection. However, obstacles arise as a result of lack of funds, economic pressures, and changes in values ​​among the younger generation. This study suggests sustainability education and cross-sector collaboration forums, strengthening sustainable economic schemes based on ecotourism and agroforestry, and contextual environmental education to maintain the sustainability of the program. These results confirm that conservation policies integrated with local wisdom and cross-sector collaboration can be an innovative model for other regions, while strengthening the paradigm of sustainable development that is responsive to the existing socio-cultural context.